Finite Element Stress Analysis of Basalt/Epoxy and Carbon/Epoxy Composite Laminate with Varying Hole Configuration - Ali, Nurhafeezah (IRC, 2018)

(untitled)
Multiple holes in different patterns are present on composite structures for fastening purposes. The presence of holes in a structure results in a high stress gradient at the vicinity of their edges. This complex stress gradient results in a complicated failure mechanism near the hole. This study is conducted to investigate the tensile strength, compressive strength, and flexural strength of basalt/epoxy and carbon/epoxy laminates, as well as to determine the effects of different hole configurations on the strength of basalt and carbon epoxy composite laminates. Finite element simulations were conducted to prove the mechanical tests. The results reveal that the strength of the basalt laminates is the highest with the specimen of bigger gap between the holes and the lowest with two holes in a closer gap between the holes. Data and other findings from this study could be helpful in providing better understanding of the effects of holes made for fastening purposes on the composite structures.